2018
DOI: 10.1038/s41598-018-23575-0
|View full text |Cite
|
Sign up to set email alerts
|

Extensive molecular tinkering in the evolution of the membrane attachment mode of the Rheb GTPase

Abstract: Rheb is a conserved and widespread Ras-like GTPase involved in cell growth regulation mediated by the (m)TORC1 kinase complex and implicated in tumourigenesis in humans. Rheb function depends on its association with membranes via prenylated C-terminus, a mechanism shared with many other eukaryotic GTPases. Strikingly, our analysis of a phylogenetically rich sample of Rheb sequences revealed that in multiple lineages this canonical and ancestral membrane attachment mode has been variously altered. The modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
(63 reference statements)
2
9
0
Order By: Relevance
“…For this purpose, we generated a Rheb mutant that lacks the C-terminal CaaX motif and therefore cannot be farnesylated but instead contains a myristoylation signal at its N-terminus (Figure 5H). This strategy was based on the following logic: 1) myristoylation, like farnesylation, supports only transient membrane interactions; 2) N-terminal myristoylation was previously shown to be an effective substitute for C-terminal farnesylation in H-Ras (Cadwallader et al , 1994); and 3) recent phylogenetic analysis identified Rheb genes in some species that lack C-terminal farnesylation but are predicted to be myristoylated at their N-termini (Zahonova et al , 2018). Interestingly, although a Rheb mutant that is neither farnesylated nor myrisotylated failed to promote mTORC1 signaling in Rheb Depleted cells, myristoylated Rheb stimulated S6K phosphorylation (Figure 5, I and J).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we generated a Rheb mutant that lacks the C-terminal CaaX motif and therefore cannot be farnesylated but instead contains a myristoylation signal at its N-terminus (Figure 5H). This strategy was based on the following logic: 1) myristoylation, like farnesylation, supports only transient membrane interactions; 2) N-terminal myristoylation was previously shown to be an effective substitute for C-terminal farnesylation in H-Ras (Cadwallader et al , 1994); and 3) recent phylogenetic analysis identified Rheb genes in some species that lack C-terminal farnesylation but are predicted to be myristoylated at their N-termini (Zahonova et al , 2018). Interestingly, although a Rheb mutant that is neither farnesylated nor myrisotylated failed to promote mTORC1 signaling in Rheb Depleted cells, myristoylated Rheb stimulated S6K phosphorylation (Figure 5, I and J).…”
Section: Resultsmentioning
confidence: 99%
“…4H). This strategy was based on the following logic: 1) Myristoylation, like farnesylation supports only transient membrane interactions; 2) N-terminal myristoylation was previously shown to be an effective substitute for C-terminal farnesylation in H-Ras (Cadwallader et al, 1994); and 3) Recent phylogenetic analysis identified Rheb genes in some species that lack C-terminal farnesylation but are predicted to be myristoylated at their N-termini (Zahonova et al, 2018). Interestingly, although a Rheb mutant that is neither farnesylated or myrisotylated failed to promote mTORC1 signaling in Rheb Depleted cells, myristoylated Rheb stimulated S6K phosphorylation ( Fig.…”
Section: N-terminal Myristoylation Can Substitute For Rheb C-terminalmentioning
confidence: 99%
“…Third, constitutively targeting TSC to lysosomes suppresses mTORC1 signaling (Menon et al, 2014). Fourth, although the Rheb protein in most commonly studied model organisms is targeted to membranes via farnesylation of a C-terminal CaaX motif, a recent phylogenetic analysis of Rheb protein sequences revealed that Rheb homologs in some species lack lipidation and are instead predicted to interact with membranes via an N-terminal FYVE domain (Zahonova et al, 2018). In others, the C-terminal CaaX motif is accompanied by an N-terminal PX domain (Zahonova et al, 2018).…”
Section: Evidence In Favor Of Dynamic Interactions Between Rheb and Ementioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing data were obtained from cultures grown at two different light regimes (in the dark and in the light) to improve the coverage of differentially expressed genes and to maximize the chance we detect possible traces of genes encoding the photosynthesis-related machinery. Data extracted from the sequenced E. longa transcriptome proved instrumental in characterizing the function of the RuBisCO enzyme in this species 23 and enabled identification of a novel Euglenozoa-specific form of the Rheb GTPase 26 , but publication of the whole transcriptome assembly has been pending.…”
Section: Introductionmentioning
confidence: 99%